Efficacy of Cellulose Film Mixed with Microencapsulation of Essential Oils Inhibited Lasiodiplodia theobromae Causing Fruit Rot of Longkong - Chuaboon, Wilawan; Pakthongchai, Jiraporn; Luckanatinvong, Voraphat; Poomipan, Phakpen; Thepsilvisut, Ornprapa; Chutimanukul, Preuk; Athinuwat, Dusit (Thai Journal of Science and Technology, 2023)
The efficacy of essential oil microcapsules in inhibiting the pathogenesis of rot fruit in longkong caused by L. theobromae testing with the Paper disc method, arrangement by a completely randomized trial (CRD). The result was found that at 24 hours, 10% of essential oil microcapsules from dill seeds with GA encapsulation has the most antifungal efficacy with the diameter colony were 2.30±1.75 cm, followed by 10% anise and 5% dill essential oil microcapsules with GA encapsulation with colonies of 3.91±0.18 and 4.03±0.03 cm, respectively, were not statistically different (P<0.05). After incubated at 48-hour found that the 5%dill essential oil with GA encapsulation remained the most effective inhibitor of fungal growth with colony were 3.66±0.22 cm. The efficacy of film cellulose mixed with microcapsules of essential oil testing with spray coating and stored at room temperature. The longkong coated with film cellulose mixed with 10% of essential oil microcapsules from dill seeds with GA encapsulation had the longest storage life to 5 days while the control can be storage life for 3 days.